Correlation Between Peripheral Blood Immune Cell Distribution and Disease Severity and Prognosis in Multiple Sclerosis Patients - Liu PJ; Yuan P; Liu SP (Journal of Inflammation Research, 2025)
Pen-Ju Liu, Peng Yuan, Shui-Ping Liu Department of Neurology, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of ChinaCorrespondence: Pen-Ju Liu, Department of Neurology, Beijing Anzhen Hospital, Capital Medical University, No. 2 Anzhen Road,Chaoyang District, Beijing, 100029, People’s Republic of China, Tel +86-13521678687, Email lpjhq@163.comObjective: This study aimed to examine the relationship between peripheral blood immune cell distribution patterns and both disease severity and prognosis in patients with multiple sclerosis (MS).Methods: We conducted a retrospective analysis of clinical data from MS patients admitted to the Neurology Department of our Hospital between March 2020 and April 2024. Data collected included gender, age (years), disease duration (months), clinical manifestations, and results from blood and cerebrospinal fluid (CSF) tests. Disease severity and prognosis were assessed using the Expanded Disability Status Scale (EDSS) and Multiple Sclerosis Functional Composite (MSFC). Spearman correlation and multivariate linear regression (adjusted for age, gender, disease duration, and MS subtype) were employed to evaluate associations.Results: Of the MS patients studied, 10.4% (n=7) exhibited abnormal CSF pressure. The mean peripheral blood leukocyte count was 6.69 × 109/L, with neutrophils predominating (64.32% of total leukocytes), followed by lymphocytes (25.54%). The Neutrophil-to-Lymphocyte Ratio (NLR) and Monocyte-to-Lymphocyte Ratio (MLR) were 3.63 ± 2.30 and 0.33 ± 0.18, respectively. Among lymphocytes, T cells were most abundant (70.37%), with CD4+T cells comprising 40.89% and CD8+T cells at 27.80%. EDSS scores showed positive correlations with monocyte percentage (P=0.027) and MLR (P< 0.001). ZMSFC scores negatively correlated with monocyte percentage (P=0.007) and positively with T lymphocyte percentage (P=0.006). Multivariate regression confirmed MLR (β = 1.02, P < 0.001) and monocyte percentage (β = 0.24, P = 0.004) as independent predictors of EDSS severity.Conclusion: In MS patients, peripheral blood immune cells are predominantly neutrophils and lymphocytes, with CD4+T and CD8+T lymphocytes being the most prevalent lymphocyte subtypes. The distribution of these immune cells correlates significantly with MS disease severity and prognosis. Our findings suggest that immune cell subsets and MLR may serve as valuable indicators for monitoring MS progression and outcomes.Keywords: immune cells, multiple sclerosis, lymphocytes, cerebrospinal fluid